Pengaruh Minuman Sari Kedelai terhadap Gejala Hot Flashes pada Perempuan Menopause - Soedjarwo, Fazar Kumaladewi; Apreliasari, Helmy; Risnawati, Risnawati (Universitas Aufa Royhan, 2024)
The most common symptom experienced by menopausal women is hot flashes. An alternative to treat menopause symptoms is phytoestrogens, which are contained in soybean juice. The aim of the research was to find out in more depth how soybean juice drinks affect hot flashes in menopausal women. This research is a quasiexperimental design research with the form of a case control pretest posttest design. The total sample in this study was 15 menopausal women who were given soybean juice drinks. The intervention was carried out for 1 month, and monitoring before and after being given the soybean juice drink had an effect. Data analysis in this study used the T test. The results of this study prove that there is a significant difference between the pre-test and post-test scores, where there is a decrease in scores, from the pre-test average of 7.5800 to 6.3133 in the post-test scores, this means that there is an influence of soybean juice drinks on hot flashes in menopausal women. Suggestions for further research are to increase the number of respondents so that two groups can be created so that the results can be compared, so that the results obtained are more significant. Apart from this, the research also suggests increasing the frequency and duration of treatment, namely giving menopausal mothers a soybean juice drink for 1 month with a frequency of 2 times per day, so that respondents can better feel the impact of giving the soybean juice drink.